A large collection of real-world pediatric sleep studies - Harlin Lee; Boyue Li; Shelly DeForte; Mark L. Splaingard; Yungui Huang; Yuejie Chi; Simon L. Linwood (Scientific Data, 2022)
Measurement(s) Polysomnogram • Electronic Health Record • Electroencephalogram Measurement • Electrocardiogram • Electrooculogram • Electromyogram Technology Type(s) Polysomnography • Electronic Health Record System • Electroencephalography (EEG) • Electrocardiography • Electrooculography • Electromyography Sample Characteristic - Organism Homo Sapiens Sample Characteristic - Environment Hospital Sample Characteristic - Location United States Of America